2022
DOI: 10.2147/jmdh.s371957
|View full text |Cite
|
Sign up to set email alerts
|

Realities of Using Drones to Transport Laboratory Samples: Insights from Attended Routes in a Mixed-Methods Study

Abstract: Purpose Drones are an emerging technology with the potential to improve laboratory logistics. This study is based on the hypothesis that the implementation of drones will benefit from an understanding of the current system and that existing transport solutions should be optimized before drone solutions are considered. It focuses on carriers transporting biological material today by car along a traditional circular route. It aims to explore how the current transport service is organized, identify a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…The contingency taxi services range from 24–60 minutes, meaning any cancelled flights would experience much slower delivery. These figures correlate with the similar study by Comtet et al [ 32 ] who also noted large benefits in journey times but suggested there may be concerns over a need for a backup system.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The contingency taxi services range from 24–60 minutes, meaning any cancelled flights would experience much slower delivery. These figures correlate with the similar study by Comtet et al [ 32 ] who also noted large benefits in journey times but suggested there may be concerns over a need for a backup system.…”
Section: Resultssupporting
confidence: 89%
“…with the similar study by Comtet et al [32] who also noted large benefits in journey times but suggested there may be concerns over a need for a backup system. A more frequent and expeditious service has the potential to provide three benefits: (i) better workflow management and control for laboratory staff and/or equipment of samples arriving for analysis; (ii) samples spend less time subjected to uncontrolled in-vehicle conditions, which may be harmful to samples (e.g., excessive temperature or vibration conditions) and affect the integrity of analysis results [52,82,83]; and (iii) reduced bleed-to-diagnosis times, which would be advantageous for any time-critical samples.…”
Section: Plos Onementioning
confidence: 56%
See 1 more Smart Citation
“…Medical transport using drones can be used in urgent situations, where the main variable that has an impact on the success of life and health saving is the breaking of barriers to reaching difficult-to-reach places. In the context of the spread of the SARS-CoV-2 virus, drones may be used to provide diagnostic screening tests [3], medicinal products, and septic materials, transport of samples [4] of biological material, as well as information campaigns on how to deal with an epidemic, quarantine, or isolation at home [5]. With the rapid development of drone-related technologies, the applications of drones have been greatly improved, and at the same time, more requirements and implementations have emerged.…”
Section: Introductionmentioning
confidence: 99%